The Influence of E-Recruitment, Employer Branding, and Compensation on Job Application Interest Among Generation Z - Juju Zuhriatusobah; Yulianita Rahayu; Muzamal Arifin; Rosmawia; Neng Anisa; Haikal M Abdullah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The increasing reliance on digital platforms and the evolving expectations of Generation Z have made factors such as e-recruitment, employer branding, and compensation critical in shaping job application interest. This study aims to examine the influence of these three factors on Job Application Interest among Generation Z. A quantitative descriptive research design was employed, with an online questionnaire distributed to 100 respondents aged 18–29 years. Data were analyzed using SPSS through multiple regression to assess the relationships among the variables. The results indicate that e-recruitment, employer branding, and compensation each have a significant positive effect on job application interest. E-recruitment facilitates access to job information, employer branding enhances organizational appeal by communicating culture and values, and compensation motivates applicants through competitive salaries and benefits. In conclusion, organizations seeking to attract Generation Z candidates should integrate effective digital recruitment strategies, strong employer branding, and competitive compensation packages, as this combined approach can increase job application interest and enhance the effectiveness of talent acquisition in a competitive labor market. Organizations should combine effective digital recruitment, strong branding, and attractive compensation to boost Generation Z’s job application interest and enhance talent acquisition effectiveness.